ИЗУЧЕНИЕ ТЕОРЕТИЧЕСКИХ АСПЕКТОВ КЛАСТЕРИЗАЦИИ ОБРАЗОВАТЕЛЬНОГО ПРОЦЕССА И ЭФФЕКТИВНОГО ПОВЫШЕНИЯ ПРАКТИЧЕСКОЙ ДЕЯТЕЛЬНОСТИ (Conferencea, 2023)
The process of implementing the development of a culture of cooperation in the student community involves organizing events to develop a culture of cooperation among students by involving them in cooperation using a cluster approach.